Upaya Meningkatkan Hasil Belajar Passing Bawah Dengan Metode Permainan Lempar Tangkap Bola Kelas XI DPIB SMKN 3 Surabaya - Debyantoro Debyantoro; Muhammad Bambang Herinanta; Mochamad Ridwan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to support the learning objectives of underhand passing for class XI DPIB SMKN 3 Surabaya through throwing and catching ball games. Classroom Action Research (CAR) is a research technique that involves collaboration between researchers and PJOK instructors at SMKN 3 Surabaya. This study consists of four parts, namely action, planning, observation, and reflection. The implementation system of this research will be completed in stages, starting from the pre-cycle, cycle I, and cycle II. The results of this study are used as a reference in efforts to improve the learning outcomes of underhand passing for class XI DPIB SMKN 3 Surabaya students through throwing and catching ball games. has produced an average percentage of 37% in the pre-cycle, 54% in cycle I, and 83% in cycle II; this shows that they have met the requirements to achieve the learning objectives targeted by the researcher. These results indicate that the use of throwing and catching ball games can improve PJOK learning outcomes, especially volleyball underhand passing.